1989
DOI: 10.1073/pnas.86.20.7895
|View full text |Cite
|
Sign up to set email alerts
|

Systemic accumulation of specific mRNAs in response to wounding in poplar trees.

Abstract: cDNAs for several transcripts that accumulate systemically in response to mechanical wounding in a hybrid poplar have been cloned. The corresponding mRNAs become abundant in the unwounded upper leaves of poplar trees whose lower leaves have been damaged. Two of the cDNA clones have been characterized by Northern and Southern blotting, and their nucleotide sequences have been determined. These clones, designated win6 (wound-inducible) and win8, are members of multigene families encoding proteins with a high deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 48 publications
2
98
0
Order By: Relevance
“…Conceivably, dGTP phosphohydrolase and the new nucleosidase may be functionally linked. BSP-win4 family proteins in poplars are encoded by a family of physically linked genes and are induced by various stress signals, namely, elevated nitrogen level, short photoperiod, or mechanical wounding; BSP proteins serve as transient nitrogen deposit in bark (Parsons et al, 1989;Clausen & Apel. 1991;Coleman et al, 1992;Davis et al, 1993).…”
Section: [Gn]x~[gas]ux~[ua]x-~dandx[uc] (Alternative Residues Arementioning
confidence: 99%
“…Conceivably, dGTP phosphohydrolase and the new nucleosidase may be functionally linked. BSP-win4 family proteins in poplars are encoded by a family of physically linked genes and are induced by various stress signals, namely, elevated nitrogen level, short photoperiod, or mechanical wounding; BSP proteins serve as transient nitrogen deposit in bark (Parsons et al, 1989;Clausen & Apel. 1991;Coleman et al, 1992;Davis et al, 1993).…”
Section: [Gn]x~[gas]ux~[ua]x-~dandx[uc] (Alternative Residues Arementioning
confidence: 99%
“…Frozen tissue culture cells or leaf material was ground to a fine powder in liquid nitrogen; total RNA was extracted by the method of Parsons et al (26), and poly(A)+ RNA was isolated by oligo(dT)-cellulose affinity chromatography (29). RNA was separated on formaldehyde gels and blotted to Hybond (Amersham) membranes according to the manufacturer's specifications.…”
Section: Rna Isolation and Analysismentioning
confidence: 99%
“…& Gray) and eastern cottonwood (Populus deltoides Marsh) have been developed for efficient production of fiber and fuel (17). In initial molecular studies of defense reactions in the P. trichocarpa x P. deltoides hybrid Hl -l1, it was shown that mRNAs encoding chitinases and other proteins accumulate systemically in plants subjected to severe wounding (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about the reaction products of chitinase on partially N acetylated chitosan suggested the similarity of these enzymes (8,9). Some of the primary structures of chitinase genes have been reported (1)(2)(3)(4)(5)(6)(7)10,11,(13)(14)(15) Bacterial strains and growth conditions. Bacillus circulans MH-K 1 was used for preparation of chitosanase.…”
mentioning
confidence: 99%